JERZY GROTOWSKI’S ACTOR TRAINING AND ITS IMPACT ON THE TAIWANESE SEARCHING THEATRE. THE CASE OF LIU JINGMIN’S EARLY EXPERIMENTS - Łabędzka, Izabella (Porównania, 2019)
Izabella Łabędzka, JERZY GROTOWSKI’S ACTOR TRAINING AND ITS IMPACT ON THE TAIWANESE SEARCHING THEATRE. THE CASE OF LIU JINGMIN’S EARLY EXPERIMENTS. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 175-194. ISSN 1733-165X. The paper is a result of several years’ research conducted in Taiwan. It presents the early years of one of the most interesting theatre groups from Taipei, You Juchang/U-Theatre/Youren Shengu, which was established in 1988 by Liu Jingmin (Liu Ruoyu). Liu Jingmin was much inspired by Jerzy Grotowski’s idea of actor’s training presented by him in Irvine (California) in the mid-eighties. The article shows how Liu Jingmin started from imitating Grotowski’s physical exercises and later she focused on understanding her native culture. She rethought many Chinese and Taiwanese forms of theatre, meditation and breathing techniques, music and dance traditions, culture of masks andreligious rituals. The aim of this paper is to describe how Liu Jingmin for more than three decades had been working on a comprehensive development of the actor through perfecting his technical skills along with their spirit. Her goal was the internal/spiritual and external/physical transformation of a performer and finally creating a beautiful person.